Respuesta :

the answer is

-16

0

-4and4

(4x-1)(4x+1)

Answer:

ac= -16

b=0

[tex](4x+1)(4x-1)[/tex]

Step-by-step explanation:

[tex]16x^2 -1[/tex]

WE write the given polynomial in standard form ax^2 + bx+c

there is no x term so we include 0x

the given expression becomes

[tex]16x^2+0x-1[/tex]

The value of a= 16 , b= 0 and c=-1

[tex]ac= a*c = 16 * (-1) = -16[/tex]

The value of b = 0

Two number to multiply to get ac = -16 are 4 and -4

When we add two numbers we will get

-4 + 4= 0

using factors -4 and 4 , the expression becomes

[tex]16x^2-4x+4x-1[/tex]

[tex](16x^2-4x)+(4x-1)[/tex]

Factor out GCF

[tex]4x(4x-1)+1(4x-1)[/tex]

[tex](4x+1)(4x-1)[/tex] is the factored form